Nutrición preventiva (2002)
ABSTRACT: Nutrition of people in modern times has been associated to the increase of chronic diseases, such as ischemic heart disease, hypertension, cancer, diabetes, cirrhosis, osteoporosis, obesity, etc. These maladies are the primary cause of mortality in the western hemisphere. Scientific evidence point out to saturated fat, sugar, salt and alcohol, as substances that should b consume moderately. Fresh fruit, vegetables, and whole cereals, with their high of dietary fiber, vitamins and antioxidants are strongly suggested as a healthy option. Current epidemiologic background promotes of people the re-education in regard to feeding habits and anticipates an outstanding benefit in public health, if an optimal intervention in preventive nutrition is achieved.